Perancangan Bentuk Penyaring Sampah Pada Alat Penyaring Sampah Sungai - Karmiati, Besse Titing (JTTM : Jurnal Terapan Teknik Mesin, 2020)
Background Improvement of river waste filtering technology currently still has many problems and constraints, ranging from the large number of river waste filtering tools that still require large amounts of power, up to large dimensions. Aim Then it is necessary to do a development by analyzing some form of filter to get the form of river waste filter in accordance with the character of the river. Method of planning and clarifying the tasks designing the product concept, designing the product form (embodiment design). Results and Discussion this research is a 4-arm ferris wheel-shaped trash filter made of aluminum plate which rotates clockwise, each arm has a capacity of 7 kg / round and the filter power requirement is 151.62 Watt. Conclusion with a capacity of 7 kg / round with a filter power requirement of 151.62 Watts to clean waste.